Fundamentals of EM Design of Radar Absorbing Structures (RAS) - Singh, Hema (Springer Singapore, 2018)
This book presents a detailed analytical formulation, and step-by-step design procedure for the electromagnetic (EM) design of radar absorbing structures (RAS). It discusses both the equivalent circuit model and Smith chart approach with illustrations to provide a clear understanding of the steps involved in designing multilayered RAS according to the desired specifications. This book is a valuable resource for beginners, academicians, and R&D engineers working in the field of RAS design and development.